High-Resolution Genomic Analysis Does Not Qualify Atypical Plexus Papilloma as a Separate Entity Among Choroid Plexus Tumors. Issue 2 (February 2015) - Japp, Anna Sophia; Gessi, Marco; Messing-Jünger, Martina; Denkhaus, Dorota; zur Mühlen, Anja; Wolff, Johannes Ernst; Hartung, Stefan; Kordes, Uwe; Klein-Hitpass, Ludger; Pietsch, Torsten
Abstract : Abstract: Choroid plexus tumors are rare neoplasms that mainly affect children. They include papillomas, atypical papillomas, and carcinomas. Detailed genetic studies are rare, and information about their molecular pathogenesis is limited. Molecular inversion probe analysis is a hybridization-based method that represents a reliable tool for the analysis of highly fragmented formalin-fixed paraffin-embedded tissue–derived DNA. Here, analysis of 62 cases showed frequent hyperdiploidy in papillomas and atypical papillomas that appeared very similar in their cytogenetic profiles. In contrast, carcinomas showed mainly losses of chromosomes. Besides recurrent focal chromosomal gains common to all choroid plexus tumors, including chromosome 14q21–q22 (harboring OTX2 ), chromosome 7q22 ( LAMB1 ), and chromosome 9q21.12 ( TRPM3 ), Genomic Identification of Significant Targets in Cancer analysis uncovered focal alterations specific for papillomas and atypical papillomas (e.g. 7p21.3 [ ARL4A ]) and for carcinomas (16p13.3 [ RBFOX1 ] and 6p21 [ POLH, GTPBP2, RSPH9, and VEGFA]). Additional RNA expression profiling and gene set enrichment analysis revealed greater expression of cell cycle–related genes in atypical papillomas in comparison with that in papillomas. These findings suggest that atypical papillomas represent an immature variant of papillomas characterized by increased proliferative activity, whereas carcinomas seem to represent a genetically distinct tumor group. Abstract : Supplemental digital content is available in the text.